Relationship selling - Johnston, Mark W.; Marshall, Greg W. (New York, NY McGraw-Hill/Irwin, 2008)
Relationship Selling focuses on creating and maintaining profitable long-term relationships with customers, highlighting the salesperson as an essential element in communicating value to customers. This same approach is used successfully at firms throughout the world-no surprise given the extensive real-world sales and consulting experience of this author team. From its numerous role-plays and pedagogical aids to its student-friendly style and stellar teaching support, Relationship Selling is a fast-rising favorite of students and instructors alike.
Includes bibliographical references and indexes
Keywords: Quan hệ công chúng